PENGELOLAAN MAKANAN SEHAT BALITA BERDASARKAN PENGETAHUAN GIZI IBU - Siti Istiharoh (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2018)
This research is intended to understanding (1) thenutrient skill level of mothers baby, (2) the managementof the healty food for babies , & (3) correlation betweenthe nutrient skill of mothers baby with the managementof the healty food for babies in Mawar posyandu in theKepundung village subdistrict of Reban the regency ofBatang Central Java. This research belongs to a kind of thecorrelation research, ex post facto. The writer used the dataaccumulation method by questionnaire & dokumentation.The writer also used two techniques to analyze this data, theyare descriptive analysis technique & hypotheses experimentto try the correlation Product Moment that previoused withthe regulation experiment analysis, they are normality &linearity. The result of this research dedicated that theirnutrient skill in the sufficient category in 53 frequency with63,10% frequency, & the management of the healty foodfor babies also in the sufficient category in 59 frequencywith the relative frequency is 70,24%. Based on the resulthypotheses experiment is correlationed that the ProductMoment is found the correlation coefficient mark of (RÂ²) isamount of 0,661 that is consultacied in r table mark, themark of n is about 84 which is significant level of 5% is0,213. So, (RÂ²) mark that found is above of r table mark is0,661 > 0,213. It means that there was correlation betweenthe nutrient skill of mothers with the management of healtyfood for babies.